1078 Regional Oxygen Saturation During Preterm Neonatal Transition. (October 2012) - Pocivalnik, M; Binder, C; Urlesberger, B; Kratky, E; Avian, A; Müller, W; Pichler, G
Abstract : Objective: To evaluate arterial and regional tissue oxygen saturation during immediate transition after birth in late preterm infants with and without respiratory support. Methods: Prospective observational study. Using nearinfrared spectroscopy, changes in regional oxygen saturation of the brain (rSO2brain) and peripheral preductal tissue (rSO2pre) were measured during the first 15 minutes of life after elective caesarean section. SpO2 and heart rate were measured continuously. Fractional tissue oxygen extraction (FTOE) was calculated for all regions. According to need for respiratory support two groups were formed, respiratory support (RS) group and normal transition (NT) group (without need for respiratory support). Positive pressure ventilation was applied with the T-piece resuscitator, oxygen was applied according to SpO2 values. The Florian Respiratory Function Monitor was used to monitor all ventilation parameter. All was recorded including videography. Results: 49 preterm infants fulfilled entry criteria, 7 had to be excluded because need for intubation. Of the remaining infants, 21 formed NT group, and 21 RS group. Heartrate showed comparable courses in both groups. SpO2, rSO2brain and rSO2pre values showed significantly different courses in the two groups, always the NT group showing higher values. FTOE course was significantly different, showing a delayed decrease in RS group. Conclusion: First systematic analysis of behaviour of regional and arterial oxygen saturation in late preterm infants with and without need for respiratory support. Infants with respiratory support showed significantly different oxygen saturation values, all were decreased compared to a normal transition group.